2021
DOI: 10.1016/j.ophtha.2020.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure, Glaucoma, and Dietary Caffeine Consumption

Abstract: Purpose: We examined the association of habitual caffeine intake with intraocular pressure (IOP) and glaucoma and whether genetic predisposition to higher IOP modified these associations. We also assessed whether genetic predisposition to higher coffee consumption was related to IOP.Design: Cross-sectional study in the UK Biobank.Participants: We included 121 374 participants (baseline ages, 39e73 years) with data on coffee and tea intake (collected 2006e2010) and corneal-compensated IOP measurements in 2009. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 51 publications
2
41
0
Order By: Relevance
“… 31 32 Nakano et al 33 reported that habitual coffee consumption was associated with a slightly lower IOP in healthy subjects. Kim et al 34 did not find causal effect of coffee drinking on IOP. They further concluded that effect of habitual caffeine consumption depended on genetic predisposition.…”
Section: Discussionmentioning
confidence: 91%
“… 31 32 Nakano et al 33 reported that habitual coffee consumption was associated with a slightly lower IOP in healthy subjects. Kim et al 34 did not find causal effect of coffee drinking on IOP. They further concluded that effect of habitual caffeine consumption depended on genetic predisposition.…”
Section: Discussionmentioning
confidence: 91%
“…The effects of an IOP-based PRS in modulating geneenvironment interactions has also been investigated in the UK Biobank dataset (n = 121 374 participants). 130 Overall, there was no association between caffeine intake and POAG risk (p > 0.1). However, the IOP PRS modified this relationship, as those in the highest IOP PRS quintile who consumed ≥321 mg/day had a 3.9-fold higher glaucoma prevalence compared to those in the lowest PRS quintile who consumed no caffeine (p = 0.0003).…”
Section: Polygenic Risk Scoresmentioning
confidence: 86%
“…IOPcc, CH, and CRF for the right and left eye were obtained from UKBB data fields 5254, 5262, 5256, 5264, 5257, and 5265 respectively. Information on IOPcc-lowering medication use was obtained from UKBB data field 20003; pre-treatment IOPcc was imputed by dividing IOPcc by 0.7 for those on IOP medication [ 18 ]. Spherical power and cylindrical power for the right and left eye were obtained from UKBB data fields 5084, 5085, 5087, and 5086 respectively.…”
Section: Methodsmentioning
confidence: 99%